2011
DOI: 10.1051/radiopro/20116557s
|View full text |Cite
|
Sign up to set email alerts
|

Application of a “Sealed Can Technique” and CR-39 detectors for measuring radon emanation from undamaged granitic ornamental building materials

Abstract: Abstract. Radon ( 222 Rn) is the most important cause of exposure to mankind due to natural radioactivity. Radon exhalation depends not only on the 226 Ra concentration in the material, but also on other factors such as mineralogy of the region, size and density of grains and porosity of the material. As building materials are one of the major sources of environmental radon, the radiological implications of the use of materials with great content of uranium must be always assessed. In this work, radon exhalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The determination of the radon activity concentration was performed using solid nuclear track detectors (SSNTD) by means of the Sealed can technique using a polycarbonate of domestic manufacture, as solid detector of nuclear tracks [25].…”
Section: Determination Of Radon Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the radon activity concentration was performed using solid nuclear track detectors (SSNTD) by means of the Sealed can technique using a polycarbonate of domestic manufacture, as solid detector of nuclear tracks [25].…”
Section: Determination Of Radon Concentrationsmentioning
confidence: 99%
“…The results of the average of the radon determination triplicates of each sample, with the respective propagated uncertainty, are shown in Table 2. The track counts were performed manually after exposure to the natural radiation detector of the samples and treatment for the revelation of tracks [25]. In Table 2 it can be observed that the uncertainties associated with samples 3, 4, 5 and 6 were around 30%, an acceptable result considering the technique used and the fact that this technique is in the implementation phase.…”
Section: Radon Activity Concentrationsmentioning
confidence: 99%
“…Such usage enhances the radon exhalation, since the distance for the radon to reach the outer surface is shorter [15].…”
Section: Radionuclide Contents In Building Materialsmentioning
confidence: 99%
“…The bulk usage of building materials tends to decrease the ratio between the 226 Ra concentration and the radon exhalation, since the gas can be trapped in the building material. In this case, the radon decays within the building structure, thus increasing the concentration of the short-lived gamma-ray emitting decay products [15]. Typical usage of materials like concrete, cement and natural gypsum falls in this category.…”
Section: Radionuclide Contents In Building Materialsmentioning
confidence: 99%
“…Most of the emanated radon originates from radium found in shallow surface layers, up to a depth of the recoil range [10]. However, due to diffusion, these flows are notably reduced in wetter soils [11]. The rate at which the emanated radon escapes into the atmosphere is measured as the exhalation rates.…”
Section: Introductionmentioning
confidence: 99%